Intraoperative determination of small intestinal viability following ischemic injury: a prospective, controlled trial of two adjuvant methods (Doppler and fluorescein) compared with standard clinical judgment. - Bulkley, G B (1981)
Two adjuvant techniques for the intraoperative assessment of small intestinal viability were compared with standard clinical judgment in a prospective, controlled study of 71 ischemic bowel segments in 28 consecutive patients operated on for acute intestinal ischemic disease. Each segment was independently assessed 15 minutes after surgical correction of the underlying lesion by: 1) standard clinical judgment; 2) Doppler-detected pulsatile mural blood flow; and 3) fluorescein ultraviolet fluorescence pattern. Viability endpoint for each segment was determined objectively by patient follow-up or "blinded" microscopic evaluation of histologically unequivocal resection specimens using criteria established by previous animal studies. Seventeen histologically equivocal specimens were excluded from the final results. Standard clinical judgment proved moderately accurate overall (89%) but would have led to a relatively high rate (46%) of unnecessary bowel resection. The Doppler technique did not increase accuracy in any category of evaluation. The fluorescein fluorescent pattern was correct in all 54 determinant bowel segments, and proved more sensitive specific, predictive, and significantly more accurate overall than either standard clinical judgment or the Doppler method. This controlled study suggests that the fluorescein technique is the method of choice for the prediction of small intestinal recovery following ischemic injury.